Neuro-inflammatory response dynamics following intestinal surgery: a mini-review - Mu, Xinhua; Sun, Tao; Shi, Haixia (Frontiers in Medicine, 2025)
This study investigates the pathophysiological mechanisms of neuroinflammation following intestinal surgery, focusing on the interplay of cytokines, glial cell activation, and neuropeptide signaling in driving inflammatory cascades. Recent advancements in neuroimaging—such as high-resolution magnetic resonance imaging and positron emission tomography—are examined for their diagnostic utility in detecting neuroinflammatory changes. Therapeutically, we evaluate the efficacy of pharmacological interventions, including Non-Steroidal Anti-Inflammatory Drugs and corticosteroids, alongside non-pharmacological approaches such as neuromodulation and traditional Chinese medicine, in mitigating neuroinflammation and improving clinical outcomes. A multidisciplinary treatment strategy is proposed, integrating targeted drug therapies with neuromodulatory techniques to address individual patient variability. Future research directions emphasize the identification of novel biomarkers, the application of precision medicine, and the development of innovative anti-inflammatory therapies. Longitudinal studies are also recommended to assess long-term neurological outcomes and quality of life in post-surgical patients. By advancing our understanding of neuroinflammatory pathways and optimizing therapeutic strategies, this study aims to enhance postoperative care and patient prognosis.